Might Heterostyly Underlie Spider Occurrence on Inflorescences? A Case Study of Palicourea rigida (Rubiaceae), a Common Shrub from Brazilian Cerrado - Suzana Diniz; Everton Tizo-Pedroso; Denise Lange; Andréa Andrade Vilela; Danielle G. Justino; Fernanda Alves Martins; Erika Germanos; Rafael Arruda; Vanessa Stefani (Psyche: A Journal of Entomology)
We carried out a research on the Palicourea rigida (Rubiaceae) inflorescences, a distylous shrub of Brazilian Cerrado. Our objective was to compare the inflorescence architectural complexity and its quality in the two floral morphs and search for any relationship with spider occurrence. In order to assess the quality of inflorescence resources, we quantified the nectar volume and its sugar concentration and the number of fruits and flowers (intact and aborted) for both inflorescence morphs with and without spiders. For the architectural heterogeneity, we quantified floral structures and inflorescence levels of branching. Spider occurrence was higher in longistylous inflorescences than in brevistylous ones. The sampled spiders were classified into the guilds ambushers, jumpers, or orb-weavers. Ambushers, jumpers, and total richness were much higher among longistylous inflorescences. We found no difference between morphs neither in volume or nectar concentration nor in amount of fruits and flowers. However, longistylous inflorescences presented greater architectural heterogeneity than brevistylous ones. Therefore, we suggested that architectural heterogeneity is an important factor underlying the occurrence of cursorial spiders on P. rigida inflorescences, which possibly arose from the relationship between refuge availability and inflorescence architecture.